2011
DOI: 10.1016/j.pain.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Smad-interacting protein 1 controls pain sensitivity via modulation of DRG neuron excitability

Abstract: The perception of pain is initiated by the transduction of noxious stimuli through specialized ion channels and receptors expressed by primary nociceptive neurons. The molecular mechanisms that orchestrate the expression and function of ion channels relevant for pain processing are poorly understood. We demonstrate here a central role of the transcription factor Smad-interacting protein 1 (Sip1/Zfhx1b/Zeb2), a 2-handed zinc finger DNA-binding protein with essential functions in neural crest and forebrain devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…At more caudal levels, this phenotype was milder although nociceptors were reduced by 40% (data not shown). These findings are reminiscent of the impaired sensitivity of Zeb2 heterozygous mice to thermaland formalin-induced pain (but not mechanical pain) due to altered ion channel expression and slight reduction of nociceptor numbers (Jeub et al, 2011;Pradier et al, 2014). While these data further reinforce the reliability of DBZEB effects, they also show that DBZEB expression triggers a stronger phenotype than removing only one allele of Zeb2, likely explaining why mechanical pain is also affected in our model.…”
Section: Resultssupporting
confidence: 61%
“…At more caudal levels, this phenotype was milder although nociceptors were reduced by 40% (data not shown). These findings are reminiscent of the impaired sensitivity of Zeb2 heterozygous mice to thermaland formalin-induced pain (but not mechanical pain) due to altered ion channel expression and slight reduction of nociceptor numbers (Jeub et al, 2011;Pradier et al, 2014). While these data further reinforce the reliability of DBZEB effects, they also show that DBZEB expression triggers a stronger phenotype than removing only one allele of Zeb2, likely explaining why mechanical pain is also affected in our model.…”
Section: Resultssupporting
confidence: 61%
“…Moreover, spontaneous seizures were observed in some mice with Zeb2 knockout in the Gsh2 expression domain (mainly LGE, CGE, and a portion of the MGE), suggesting that Zeb2 knockout in LGE, CGE and MGE-derived interneurons is more detrimental than in MGE alone . Similarly, the underreaction to pain reported in some MWS patients (Evans et al, 2012), likely reflects the reduced responsivity of DRG nociceptors observed in heterozygous Zeb2 mice (Jeub et al, 2011;Pradier et al, 2014), as well as in adult mice expressing a dominantnegative ZEB protein (Ohayon et al, 2015). Finally, a rare MWScausing Zeb2 mutant led to the demonstration that Zeb2 and NuRD functionally interact during neural induction, suggesting that defective NuRD recruitment can cause MWS (Verstappen et al, 2008).…”
Section: Zeb2 Mutant Mice and Mowat-wilson Syndromementioning
confidence: 99%
“…In addition to roles in cell fate determination, Zeb2 has been reported to modify the electrophysiological properties of nociceptive primary sensory neurons of the mouse dorsal root ganglion (DRG) (Jeub et al, 2011). Jeub et al (2011) showed that heterozygous Zeb2 mice displayed reduced thermal pain responses, which were subsequently attributed to Zeb2 regulation of voltage-gated ion channels that, in turn, modulated the excitability of DRG nociceptors.…”
Section: Zeb2 In Spinal Cord Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the initial painful sensation after capsaicin application arises from the selective activation of TRPV1 (transient receptor potential ion channel of vanilloid subtype-1), which is mainly expressed in sensory neurons. It is reported that the inhibition of I A by inflammatory mediators increases the excitability of nociceptor and leads to pain and hyperalgesia (Liu et al 2001; Jeub et al 2011). To determine whether the VGPCs might contribute to the pain induced by capsaicin, we investigated how capsaicin modulated I A in rat TG neurons previously.…”
Section: Introductionmentioning
confidence: 99%